Analisis Komitmen Organisasi Berdasarkan Faktor Kepemimpinan Dan Budaya Organisasi Kerja Pada Aparatur Sipil Negara (ASN) - Ricky Satria (Journal of Business and Economics (JBE) UPI YPTK, 2022)
This study aims to test how much influence the leadership and culture of the work organization on organizational commitment with job satisfaction as an intervening variable in the State Civil Apparatus (ASN) Dagperinkopukm Office of Sijunjung Regency. Data collection methods through surveys and distributing questionnaires, sample delay 49 response. The analysis method used is the path analysis using Smartpls 3. The results of the study found that leadership had a positive and significant effect on job satisfaction. Organizational culture has a positive effect and has a significant amount of job satisfaction. Leadership has a positive and significant effect on organizational commitment. Organizational culture has a positive and significant effect on organizational commitment. Job satisfaction does not have a positive effect and is self-conflict on organizational commitment. Job satisfaction does not mediate the influence of leadership on organizational commitment. Job satisfaction does not mediate the influence of the culture of the organization in organizational commitment. The contribution of the independent variable contribution of leadership, organizational culture, and job satisfaction to the dependent variable of organizational commitment is 97.9%. While the remaining 2.1% is influenced by other variables outside of this study.